PENGARUH KEMAMPUAN KOMUNIKASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN OGAN KOMERING ULU (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The purpose of this study was to determine the effect of the influence of communicationskills and work discipline on employee productivity at the Trade and Industry Service ofOgan Komering Ulu Regency. The analytical tool used is multiple linear regression. Theresults of this study are simultaneously and partially there is a significant effect betweenCommunication Capabilities and Work Discipline on Employee Productivity in the Officeof Trade and Industry of Ogan Komering Ulu Regency. The percentage of the effect of theinfluence of Communication Skills and Work Discipline on Employee Work Productivityat the Department of Trade and Industry in Ogan Komering Ulu Regency is 96.7% whilethe remaining 3.3% is influenced or explained by other variables not included in thisresearch model for example Training.